Concepciones de los profesores sobre la enseñanza de las ecuaciones diferenciales a estudiantes de química y biología. Estudio de casos - Moreno, M.; Azcárate, Carmen (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
Intending to quest about the conceptions math teachers hold about how to teach Differential Equations to chemistry and biology students, we have devised a research tool which allows us to derive relevant information. We use different means to collect the adequate data related to the qualitative research, targeting the exploration of what teachers «say they do» and what «they do and would like to do». The use of concept maps and a questionnaire, along with a recorded interview, has revealed itself as an accurate means for the appropriate analysis of data, as shown in the case study we hereby include.